Synthetic Polymer Tag for Intracellular Delivery of siRNA. Issue 7 (29th May 2018) - Tai, Wanyi; Gao, Xiaohu
Abstract: Short interference RNA (siRNA) is capable of precisely controlling the expression levels of virtually any functional genes. Before tapping into the full potential of siRNA, however, the longstanding difficulty of cell type‐specific cytosolic delivery of siRNA must be addressed. Conventional cationic materials are unsuitable because of their toxicity, colloidal instability, large and heterogeneous complex sizes, and interference with targeting. Building on the new concept of tagging individual siRNA‐targeting ligand chimera with charge–neutral endosomolytic agents, a new class of tags based on synthetic polymers is developed. Compared to multifunctional proteins and peptides previously made for the same functions, the synthetic polymer tags are simple and inexpensive to make, compact in size, have a low immunogenic potential, and are stable in circulation. Efficient in vitro and in vivo gene silencing is achieved, opening exciting opportunities for development of targeted biologics. Abstract : A charge–neutral endosomolytic polymer is developed to tag short interference RNA (siRNA)‐targeting ligand chimera for targeted cytosolic delivery of siRNA. The polymer tag is simple to make, compact in size, biocompatible, stable in circulation, and low‐cost, opening exciting opportunities for clinical translation.